Accelerating Student and Staff Learning : Purposeful Curriculum Collaboration. - Psencik, Margaret Kay (SAGE Publications, 2009)
This targeted staff development approach helps teachers collaborate in professional learning teams to gain a deep understanding of content and create a school-based curriculum tied to standards.